Prognostic analysis of cuproptosis-related gene in triple-negative breast cancer - Sha, Shengnan; Si, Luyi; Wu, Xinrui; Chen, Yuanbiao; Xiong, Hui; Xu, Ying; Liu, Wangrui; Mei, Haijun; Wang, Tao; Li, Mei (Frontiers in Immunology, 2022)
Backgroud:Cuproptosis is a regulatory mechanism for cell death that has never been observed before and is associated with tumor progression, prognosis, and immune response. However, the potential role of cuproptosis-associated genes (CRGs) in the tumor microenvironment (TME) remains unclear. Patients and methods:A total of 346 samples of triple-negative breast cancer (TNBC) were collected from TCGA and three GEO databases, and were classified and signed by R-package. Then we analyzed the relationships between the different subgroups and clinical pathological characteristics, immune infiltration characteristics and mutations of TME. Finally, a nomogram and calibration curve were constructed to predict the patient's survival probability in order to improve the clinical applicability of CRG_score. Results:We identified two CRG clusters, with immunocyte infiltration characteristics that were highly consistent with those of the immune-inflamed and immune-desert clusters, respectively. Further, we demonstrated that gene signature can be used to evaluate tumor immune cell infiltration, clinical features of patients and prognostic status. Low CRG_Score, characterized by H-TMB and immune activation, has a good survival probability and was more immunoreactive to CTLA4, while high CRG_Score was characterized by the activation of stromal pathways and immunosuppression. Conclusion:Our research revealed the potential role of CRGs in tumor microenvironment, clinicopathological features and prognosis. The newly discovered cuproptosis-related gene was closely related to the tumor immunity of triple-negative breast cancer, and it could be a tool for predicting the potential prognosis of triple-negative breast cancer, and provided a target and research idea for the development of related drugs in the future.